2014
DOI: 10.1021/la5025229
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Unsupported Shaped Palladium Nanoparticles

Abstract: The potential range in which hydrogen electro-adsorption, electro-absorption, and evolution reaction occur is examined in an acidic medium using cyclic-voltammetry (CV) and Pd nanoparticles with controlled size and shape distributions. The three processes give rise to unique features in CV profiles and are observed in distinct potential ranges. This behavior is not observed for bulk Pd materials and arises due to the nanoscopic nature of the Pd materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 32 publications
8
62
0
Order By: Relevance
“…In order to clean the Pd catalyst the procedure suggested by Zalineeva et al was used [14]. Finally the catalyst was filtered, washed several times with water and dried overnight at 75 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to clean the Pd catalyst the procedure suggested by Zalineeva et al was used [14]. Finally the catalyst was filtered, washed several times with water and dried overnight at 75 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The enhanced electrocatalytic properties are suggested to arise not from their crystallographic structure, but from the adsorbed polyallylamine that is used in the synthesis of these Pd particles. Recently, it has been shown that the activity of hydrogen evolution reaction depends on the shape of Pd nanoparticles [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the whole group of Pd binary alloys, which are known as good catalysts and hydrogen absorbers [1][2][3][4][5][6], two systems deserve a special attention, namely Pd-Rh and Pd-Ru alloys. These systems are exceptional, because for certain composition ranges, the maximum amounts of absorbed hydrogen are greater than in the case of pure Pd [1][2][3][4][5][6][7][8][9][10][11][12][13][14], while other Pd alloys in their full composition range are always characterized by a weaker maximum ability to absorb hydrogen [1][2][3][4][5][6][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These systems are exceptional, because for certain composition ranges, the maximum amounts of absorbed hydrogen are greater than in the case of pure Pd [1][2][3][4][5][6][7][8][9][10][11][12][13][14], while other Pd alloys in their full composition range are always characterized by a weaker maximum ability to absorb hydrogen [1][2][3][4][5][6][15][16][17][18][19]. In most Pd alloys, the gaps in the Pd d-band are filled by the electrons originating from the alloying metal, and therefore, less electronic states remain free for the electrons to be accepted from absorbing hydrogen, which leads to a deterioration of the absorption capacity [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation